Is propofol a safe and effective sedative for relocating hip prostheses?. Issue 1 (22nd December 2008) - Mathieu, N; Jones, L; Harris, A; Hudson, A; McLauchlan, C; Riou, P; Lloyd, G
Abstract : Objective: To explore the safety and efficacy of propofol as a sedative for the relocation of hip prostheses in the emergency department. Methods: A prospective observational study was performed in 100 patients aged 37–93 years who received sedation with propofol in the emergency department for hip prosthetic relocation. All patients received intravenous titrated morphine prior to radiography, followed by a 1 mg/kg bolus of propofol after adequate preoxygenation. At 60 s, joint relocation was attempted by an independent physician. Data for each patient were recorded, with particular attention given to adverse outcomes. Results: Two patients were excluded because of protocol violation. The use of propofol achieved hip relocation in 94 of the remaining 98 patients (96%). The four unsuccessful cases required general anaesthesia with muscle relaxation. Eight patients experienced a fall in oxygen saturation, four responding to airway repositioning and four requiring brief supplemental ventilation. Four patients became hypotensive and required titrated intravenous boluses of a vasopressor (metaraminol) to restore normal blood pressure. 42 patients required additional doses of propofol, 36 for inadequate sedation and 6 for prolonged reduction attempts. Conclusions: Significant adverse effects of propofol in this case series were uncommon (12/98 patients) and readily countered. This case series suggests that propofol is a safe and effective sedative for relocating hip prostheses.